Design thinking-based needs analysis for developing AR- and gamification-enhanced learning media to improve vocational students’ numeracy skills - Rahmawati, Lu'lu Imania; Purwosetiyono, F. X. Didik; Dwijayanti, Ida (Universitas Islam Negeri Raden Intan Lampung, 2026)
Numeracy is a crucial competency for high school students, but many students struggle with contextual numeracy problems because they use interactive learning media infrequently. This study aims to analyze the learning needs of vocational high school students and design innovative solutions to improve their numeracy skills. The key innovative aspect of this study lies in integrating design thinking, Augmented Reality (AR), and gamification approaches on the Assemblr Edu and Kahoot (ALOOT) platforms. The methodological approach used is qualitative, integrating the empathizing, defining, and ideation phases of Design Thinking with meta-analysis. Participants included 101 students and 9 mathematics teachers. The initial study results indicated that students face significant challenges in understanding contextual numeracy problems due to the inherent limitations of interactive media. A meta-analysis of 10 relevant articles revealed a highly significant effect of AR and gamification on numeracy skills, with an effect size of 1,400, indicating a very large effect. The practical implications of this research include developing user-centered instructional media guidelines, increasing student engagement and active motivation through interactive learning, and strengthening the relevance of numeracy content to real-world work and the vocational contexts faced by vocational high school students.